The Effect of Training Model and Tennis Skill Level on Concentration and Groundstroke Skills in Tennis Athletes - Cahyadi, Rendy Aditya; Mu'mun, Amung; Budiana, Dian (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
The rhythm training model is a new training model applied in Indonesia, especially in tennis. The rhythmic movements that are applied using a metronome are designed to improve motor movement, focus, concentration, and increase the athlete's confidence. The purpose of this study was to examine the effect of the rhythm exercise model on groundstroke and concentration in tennis athletes. The researcher used the experimental method, with the research design used in this study being a 2x2 factorial design. 24 tennis athletes were selected using the purposive sampling method. The instruments used are Hewitt's Tennis Achievement Test For Groundstroke to measure groundstroke in tennis and Concentration Grid Test to measure concentration level. The results of this study found that there was a difference in the effect between the rhythm training model and the non-rhythmic training model on groundstroke skills and concentration levels in tennis athletes.